Depletion of trypanosome CTR9 leads to gene expression defects - Benard Aswani, Ouna; Nyambega, Benson; Manful Gwira, Theresa; Helbig, Claudia; Maleš, Matilda; Fadda, Abeer; Clayton, Christine (PLOS ONE, 2012)
The Paf complex of Opisthokonts and plants contains at least five subunits: Paf1, Cdc73, Rtf1, Ctr9, and Leo1. Mutations in, or loss of Paf complex subunits have been shown to cause defects in histone modification, mRNA polyadenylation, and transcription by RNA polymerase I and RNA polymerase II. We here investigated trypanosome CTR9, which is essential for trypanosome survival. The results of tandem affinity purification suggested that trypanosome CTR9 associates with homologues of Leo1 and Cdc73; genes encoding homologues of Rtf1 and Paf1 were not found. RNAi targeting CTR9 resulted in at least ten-fold decreases in 131 essential mRNAs: they included several that are required for gene expression and its control, such as those encoding subunits of RNA polymerases, exoribonucleases that target mRNA, RNA helicases and RNA-binding proteins. Simultaneously, some genes from regions subject to chromatin silencing were derepressed, possibly as a secondary effect of the loss of two proteins that are required for silencing, ISWI and NLP1.
Gesehen am 26.04.2018